Changes in substrate utilisation and protein catabolism during multiday cycling in well-trained cyclists - Oosthuyse, T.; Avidon, I. (Journal of Sports Sciences, 2015)
There is a paucity of studies that have evaluated substrate utilisation and protein catabolism during multiday strenuous exercise in athletes. Eleven well-trained male cyclists completed 3 h of race-simulated cycling on 4 consecutive days. Cyclist exercised 2 h postprandially and with carbohydrate supplementation (~50 g/h) during exercise. Whole body substrate utilisation was measured by indirect calorimetry, protein catabolism from sweat and urine urea excretion, and blood metabolite concentration was evaluated. Protein catabolism during exercise was significantly greater on days 2-4 (29.9 ± 8.8; 34.0 ± 11.2; 32.0 ± 7.3 g for days 2, 3, and 4, respectively) compared to day 1 (23.3 ± 7.6 g), P < 0.05. Fat oxidation was greater at 21 km (~45 min) on days 2-4 (1.06 ± 0.23; 1.08 ± 0.25; 1.12 ± 0.29 g/min) compared to day 1 (0.74 ± 0.23 g · min-1, P < 0.05), but the rate of carbohydrate and fat oxidation was similar between days at 50 and 80 km. Whole body substrate utilisation is altered on subsequent days of multiday prolonged strenuous cycling that includes a quicker transition to greater fat utilisation from exercise onset and a 28-46% greater reliance on endogenous protein catabolism on all successive days.